Pengaruh Literasi Keuangan, Fintech Payment Gateway Terhadap Peningkatan Pendapatan UMKM di Kota Palembang. - Fawaz Taufiqurrahman; Ade Kemala Jaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of financial literacy, fintech payment gateways on increasing the income of MSMEs in Palembang City. The scope of the study includes businesses run by MSMEs in several malls, namely PS Mall, OPI Mall, IP Mall, and PTC Mall. Primary data was collected through the distribution of Google Form-based questionnaires to 100 respondents. Data analysis was carried out using the SmartPLS4 application through a multivariate statistical approach Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study indicate that partially, the financial literacy variable has a significant positive effect on increasing income. Meanwhile, payment gateways also have a significant positive effect. This study is expected to contribute and serve as a reference in running businesses that will be run by MSMEs. The novelty of the study lies in the focus of the study area, namely in several malls that have been mentioned and are located in Palembang City, as well as the novelty of the use of testing tools in previous studies that use SPSS linear regression.